Accident Scenarios Involving Pebble Bed High Temperature Reactors. Issue 1 (2nd January 2017) - Englert, Matthias; Frieß, Friederike; Ramana, M. V.
ABSTRACT: Proponents of high temperature gas cooled reactors argue that the reactor type is inherently safe and that severe accidents with core damage and radioactive releases cannot occur. The argument is primarily based on the safety features of the special form of the fuel. This paper examines some of the assumptions underlying the safety case for high temperature gas cooled reactors and highlights ways in which there could be fuel failure even during normal operations of the reactor; these failures serve to create a radioactive inventory that could be released under accident conditions. It then describes the severe accident scenarios that are the greatest challenge to high temperature gas cooled reactor safety: ingress of air or water into the core. Then, the paper offers an overview of what could be learned from the experiences with high temperature gas cooled reactors that have been built; their operating history indicates differences between actual operations and theoretical behavior. Finally, the paper describes some of the multiple priorities that often drive reactor design, and how safety is compromised in the process of optimizing other priorities.